Increasing Purchase Intention in Digital Marketing for the Premium Real Estate Industry: The Role of Brand Image, Product Quality, Service Quality, and Customer Satisfaction - Sausan Nabilla Malich; Tony Antonio; Trianggoro Wiradinata (Publikasi Indonesia, 2026)
This study analyzes the influence of digital marketing on purchase intention in the premium property industry, examining the mediating role of brand image, perceived product quality, perceived service quality, and customer satisfaction. Using an explanatory quantitative approach, data were collected via an online questionnaire from 110 prospective Developer C consumers categorized as qualified leads who had completed a site visit. Saturated (total) sampling was applied, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. Results show that digital marketing has a positive and significant effect on brand image, perceived product quality, and perceived service quality in the pre-purchase phase. However, in shaping customer satisfaction, only perceived product quality emerges as the dominant functional determinant and the sole significant mediator; brand image and perceived service quality fail to mediate the relationship, as premium property consumers evaluate them merely as minimum hygiene factors. Customer satisfaction, in turn, significantly mediates the relationship between perceived product quality and purchase intention, but not the paths from brand image or service quality. These findings confirm that in high-involvement industries, purchase intention is driven by functional satisfaction with the product's physical quality rather than emotional preference for the developer's reputation. Developer C management is therefore advised to prioritize product quality control and maintain consistency between digital information visualization and physical reality during site visits to minimize gaps in consumer expectations.